SFas and FasL in etiopathogenesis of autoimmune diseases of the thyroid gland and nodular forms of goiter - M. I. Sheremet (Journal of Education, Health and Sport, 2015)
Sheremet М. І., Shidlovskyy V. О., Girla Y. V., Tkachuk N. P., Tibirna A. G., Dorosh V. P. SFas and FasL in etiopathogenesis of autoimmune diseases of the thyroid gland and nodular forms of goiter. Journal of Education, Health and Sport. 2015;5(12):41-49. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34845 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A41-49